Analisis Teori Pariwisata Penjelajahan Diri dan Transformasi terhadap Kunjungan Turis di Krui, Kabupaten Pesisir Barat, Provinsi Lampung - Tita Nurhayatun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article analyses the impact of Self-Exploration and Transformation Tourism Theory on tourist arrivals in Krui, West Pesisir Regency, Lampung. The background of this research is the tourism potential of Krui, which is famous for its beautiful beaches and rich local culture. The method used is a descriptive qualitative approach with in-depth interviews and direct observation. The results showed that tourism in Krui experienced an increase in visits after the COVID-19 pandemic, fuelled by various promotional initiatives and improved facilities. The self-exploration and transformation theory of tourism is relevant to Krui, as the tourism experience there can support tourists' self-reflection and personal growth. Interaction with the natural environment and local culture in Krui provides a deep and meaningful experience in line with the principles of this theory. This article highlights the importance of sustainable tourism management to maintain a balance between economic benefits and environmental conservation..